Perception, causation, and objectivity - Roessler, Johannes; Lerman, Hemdat; Eilan, Naomi (Oxford : Oxford University Press, 2011)
Leading philosophers & psychologists offer an assessment of the commonsense view that perceptual experience is an immediate awareness of mind-independent objects. They examine the nature of perception, its role in the acquisition of knowledge, the role of causation in perception, & how perceptual understanding develops in humans.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Perception (Philosophy); Causation; Objectivity